Age reprogramming and epigenetic rejuvenation - Prim B. Singh; Andrew G. Newman (My University, 2018)
Age reprogramming represents a novel method for generating patient-specific tissues for transplantation. It bypasses the de-differentiation/redifferentiation cycle that is characteristic of the induced pluripotent stem (iPS) and nuclear transfer-embryonic stem (NT-ES) cell technologies that drive current interest in regenerative medicine. Despite the obvious potential of iPS and NT-ES cell-based therapies, there are several problems that must be overcome before these therapies are safe and routine. As an alternative, age reprogramming aims to rejuvenate the specialized functions of an old cell without de-differentiation; age reprogramming does not require developmental reprogramming through an embryonic stage, unlike the iPS and NT-ES cell-based therapies. Tests of age reprogramming have largely focused on one aspect, the epigenome. Epigenetic rejuvenation has been achieved in vitro in the absence of dedifferentiation using iPS cell reprogramming factors. Studies on the dynamics of epigenetic age (eAge) reprogramming have demonstrated that the separation of eAge from developmental reprogramming can be explained largely by their different kinetics. Age reprogramming has also been achieved in vivo and shown to increase lifespan in a premature ageing mouse model. We conclude that age and developmental reprogramming can be disentangled and regulated independently in vitro and in vivo.
Keywords: Age reprogramming; Epigenetic rejuvenation; Somatic cell nuclear transfer (SCNT); iPS cells; Reprogramming factors; Epigenetic clock; eAge